The Life of José María Sobral Scientist, Diarist, and Pioneer in Antarctica - Tahan, Mary R. (Springer Biographies, 2018)
Featuring the previously unpublished diary of José María Sobral, Under-Lieutenant of the Argentine Navy, this book provides insight on his life and his participation in Otto Nordenskjöld's Swedish Antarctic Expedition of 1901-1903. This biography highlights Sobral's personal thoughts on the mission, his position, the science being discovered, and the geopolitical situation around him. The reader also learns about the state of science, Antarctic exploration, and cultural-political-issues at that time. The author's critical and contextual analysis of the diary explains more about Sobral and his role in Argentina, Antarctica, science and history. This paints a detailed picture of Sobral as an individual, and provides the framework to depict the world in which Sobral lived and worked as well as his expedition and accomplishments. The book aims to explain the context of Sobral's writings, the significance of the events he described in his diary entries, and the way all of these events tied into history and scientific discovery.